(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Una proposta di disciplina sugli enti religiosi. Gli obiettivi - 2. Sulla qualificazione degli enti come religiosi. I problemi - 3. Verso la qualificazione degli enti religiosi. La proposta. Religious bodies and regulatory gaps. A law proposal ABSTRACT: The article is about the discipline of some figures of religious entities provided for in the law proposal on religious freedom in Italy drawn up by an Astrid study group. It considers the basic choices made by the proposal and why it focuses fundamentally on two figures - churches and associations with a main and prevalent purpose of religion or worship - developing definitions and distinctions to fill regulatory gaps, to overcome old norms, to integrate new norms.